On the multiday haze in the Asian continental outflow: the important role of synoptic conditions combined with regional and local sources - Seo, Jihoon; Kim, Jin Young; Youn, Daeok; Lee, Ji Yi; Kim, Hwajin; Lim, Yong Bin; Kim, Yumi; Jin, Hyoun Cher (COPERNICUS GESELLSCHAFT MBH, 2017)
The air quality of the megacities in populated and industrialized regions like East Asia is affected by both local and regional emission sources. The combined effect of regional transport and local emissions on multiday haze was investigated through a synthetic analysis of PM2.5 sampled at both an urban site in Seoul, South Korea and an upwind background site on Deokjeok Island over the Yellow Sea during a severe multiday haze episode in late February 2014. Inorganic components and carbonaceous species of daily PM2.5 samples were measured, and gaseous pollutants, local meteorological factors, and synoptic meteorological conditions were also determined. A dominance of fine-mode particles (PM2.5 / PM10 similar to 0.8), a large secondary inorganic fraction (76 %), high OC / EC (> 7), and highly oxidized aerosols (oxygen-to-carbon ratio of similar to 0.6 and organic-mass-to-carbon ratio of similar to 1.9) under relatively warm, humid, and stagnant conditions characterize the multiday haze episode in Seoul; however, the early and late stages of the episode show different chemical compositions of PM2.5. High concentrations of sulfate in both Seoul and the upwind background in the early stage suggest a significant regional influence on the onset of the multiday haze. At the same time, high concentrations of nitrate and organic compounds in Seoul, which are local and highly correlated with meteorological factors, suggest the contribution of local emissions and secondary formation under stagnant meteorological conditions to the haze. A slow eastward-moving high-pressure system from southern China to the East China Sea induces the regional transport of aerosols and potential gaseous precursors for secondary aerosols from the North China Plain in the early stage but provides stagnant conditions conducive to the accumulation and the local formation of aerosols in the late stage. A blocking ridge over Alaska that developed during the episode hinders the zonal propagation of synoptic-scale systems and extends the haze period to several days. This study provides chemical insights into haze development sequentially by regional transport and local sources, and shows that the synoptic condition plays an important role in the dynamical evolution of long-lasting haze in the Asian continental outflow region.
Keywords: POLYCYCLIC AROMATIC-HYDROCARBONS; SECONDARY ORGANIC AEROSOL; DICARBOXYLIC-ACIDS; SOURCE IDENTIFICATION; CHEMICAL CHARACTERISTICS; PARTICULATE MATTER; SAMPLING ARTIFACTS; MOLECULAR MARKER; AIR-POLLUTANTS; EASTERN CHINA